The impact of membership in competing alliance constellations: Evidence on the operational performance of global airlines - Lazzarini, Sérgio G. (Strategic Management Journal, 2007)
Abstract Many industries have witnessed the formation of multiple‐partner alliances or constellations competing against each other for both clients and members. Using the global airline industry as an empirical setting, I evaluate the proposition that membership in airline constellations allows carriers to capture externalities from other firms in the form of direct or indirect traffic flow, thereby enhancing their operational performance. I also distinguish between two ways to demarcate the boundaries of constellations: explicitly or implicitly. Analyzing patterns of membership in explicit constellations involving formal, multilateral agreements (such as the Star Alliance, Oneworld, SkyTeam), I find that membership benefits are greatest in groups involving large aggregate traffic and for carriers contributing with a large portion of the group's capacity. I also evaluate patterns of membership in implicit constellations, corresponding to groups of firms showing relatively more ties to one another than to firms outside their group. I find that carriers bilaterally linked with key players of such groups are able to increase their operational performance even if they do not belong to any explicit constellation. Thus, results show that it is worth analyzing distinct patterns of membership simultaneously, because they are likely to have distinct implications for firm performance. Copyright © 2007 John Wiley & Sons, Ltd.